2021
DOI: 10.1111/1754-9485.13266
|View full text |Cite
|
Sign up to set email alerts
|

Medical imaging education opportunities for junior doctors and non‐radiologist clinicians: A review

Abstract: Medical imaging plays a critical role in clinical decision-making across disciplines, and as such, there is frequent need for non-radiologist clinicians to interact with medical imaging. This review examines the literature about the delivery of medical imaging education to non-radiologist clinicians, spanning junior doctors, advanced trainees and specialists. Knowledge of medical imaging among non-radiologist clinicians is paramount to the quality of patient care, with calls for formal implementation of radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A notable strength of our study is using 3D segmentation as interpretation even as a non-radiologist clinician. As such, there is a demand for the delivery of more medical imaging education at all levels, ranging from medical students to non-radiologist specialists (Ayesa et al, 2021). 3D segmentation may be an engaging and complementary teaching tool that is able to effectively train doctors and students in radiological interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable strength of our study is using 3D segmentation as interpretation even as a non-radiologist clinician. As such, there is a demand for the delivery of more medical imaging education at all levels, ranging from medical students to non-radiologist specialists (Ayesa et al, 2021). 3D segmentation may be an engaging and complementary teaching tool that is able to effectively train doctors and students in radiological interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Ayesa et al also highlighted the lack of more formal medical imaging education at all levels of medical training, from medical students to non‐radiologist specialists, as well as the critical role of medical image interpretation even as a non‐radiologist clinician. As such, there is a demand for the delivery of more medical imaging education at all levels, ranging from medical students to non‐radiologist specialists (Ayesa et al, 2021). 3D segmentation may be an engaging and complementary teaching tool that is able to effectively train doctors and students in radiological interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…We employed Web-based training due to the constraints of the SARS-CoV-2 pandemic on in-person meetings at our institution. Web-based radiology training has been piloted in a variety of educational programs with mixed results [20][21][22]. There is some suggestion that Web-based learning impairs tacit learning which is an important means of skill transfer.…”
Section: Discussionmentioning
confidence: 99%
“…In another study that surveyed interns on their experience learning radiology in medical school, 52% reported that the education was not sufficient to prepare them upon graduating [ 46 ]. A randomized trial examined 100 senior medical students who had a medical imaging learning pathway incorporated into their curriculum [ 46 ]. They spent a minimum of 8 hours learning radiology, as well as adaptive learning tutorials on clinical use and imaging interpretations.…”
Section: Reviewmentioning
confidence: 99%
“…They spent a minimum of 8 hours learning radiology, as well as adaptive learning tutorials on clinical use and imaging interpretations. The conclusion of the study found that students in the clinical phase had greater learning benefits than those in the pre-clinical phase, and the former completed the tasks in less time [ 46 ]. The sensitivity in finding pathologies in chest radiographs was between 20% and 65% in one emergency department [ 47 ].…”
Section: Reviewmentioning
confidence: 99%